(untitled) (Journal of Kidney Cancer, 2023)
Translocation and transcription factor E3 (TFE3)-rearranged renal cell carcinoma (RCC) is a rare subtype of RCCs characterised by the fusion of the TFE3 transcription factor genes on chromosome Xp11.2 with one of the multiple genes. TFE3-rearranged RCC occurs mainly in children and adolescents, although middle-aged cases are also observed. As computed tomography (CT)/magnetic resonance imaging (MRI) findings of TFE3-rearranged RCC overlap with those of other RCCs, differential diagnosis is often challenging. In the present case reports, we highlighted the features of the fluorine-18-labelled fluorodeoxyglucose positron emission tomography with CT (FDG PET-CT) in TFE3-rearranged RCCs. Due to the rarity of the disease, FDG PET-CT features of TFE3-rearranged RCC have not yet been reported. In our cases, FDG PET-CT showed high standardised uptake values (SUVmax) of 7.14 and 6.25 for primary tumours. This might imply that TFE3-rearranged RCC has high malignant potential. This is conceivable when the molecular background of the disease is considered in terms of glucose metabolism. Our cases suggest that a high SUVmax of the primary tumour is a clinical characteristic of TFE3-rearranged RCCs.